"Pit Brow Lasses" from Ackers Whiteley Colliery, Wigan c. 1890
1890 1880-1914 ""Pit Brow Lasses" from Ackers Whiteley Colliery, Wigan c. 1890" [T0031.jpg], c. 1890 These women worked at the colliery surface, screening coal, loading tubs, etc. and wore clogs, short aprons and trousers which were safer near machinery. In 1886, there were 4131 women in colliery work, earning between 1-1½ shillings [5-7½p] per day.